Role of emotional intelligence in managerial effectiveness: An empirical study - Md. Sahidur Rahman; Md. Aftab Uddin; Mostafizur Rahman (Management Science Letters)
Emotional intelligence is very critical to the managerial effectiveness. The present study intends to explore the relationships between emotional intelligence and the three roles such as, interpersonal, informational, and decision of managerial effectiveness. Emotional intelligence is measured by using the Emotional Quotient Index (Rahim et al., 2002) [Rahim, M., Psenicka, C., Polychroniou, P., Zhao, J., Yu, C., Chan, K., Susana, K., Alves, M., Lee, C., Rahman, M.S., Ferdausy, S., & Wyk, R. (2002). A model of emotional intelligence and conflict management strategies: a study in seven countries. International Journal of Organizational Analysis, 10(4), 302-326.] while managerial effectiveness is assessed by using Tsui’s (1984) scale [Tsui, A.S. (1984). A role set analysis of managerial reputation. Organizational Behavior and Human Performance, 34, 64-96.]. Data were collected by distributing self-administered questionnaires among the working MBA students using a convenience sampling technique. Respondents are asked to rate their emotional intelligence and managerial effectiveness scales. Finally 127 usable responses are received and, then, analyzed by using the descriptive statistics, bivariate correlation, and regression analysis. Analysis shows that emotional intelligence was positively related with interpersonal role, informational role, and decision role. The main implication is that emotional intelligence could enhance managerial effectiveness guiding the managers, academics, and professionals. The limitations are the sample size and the sampling technique which might limit the generalizability of the findings. Future directions are also discussed.